Short-term endoscopic alterations of early gastric cancer after successful eradication of Helicobacter pylori - Xiaohan Yan; Jingze Li; Zehua Zhang; Bensong Duan; Meidong Xu; Qinwei Xu (BMC Gastroenterology)
Abstract Background Detecting and demarcating early gastric cancers (EGC) after eradication therapy of Helicobacter pylori (H. pylori) is a challenging task due to the fact that the lesion’s surface is covered with gastritis-like tissue (non-neoplastic epithelium covering the cancerous tissue). However, our study aimed to investigate the endoscopic alterations of EGC within 3 months after eradication, which has not been reported clearly yet. Methods Consecutive EGC patients who underwent two gastroscopies (one with H. pylori infection and another within 3 months after successful H. pylori eradication) were enrolled. The endoscopic photographs were evaluated for the endoscopic features and confidence level of demarcation line (DL), invasion depth, and histopathological classification by three highly experienced endoscopists. The DL estimated by endoscopy was compared with that of postoperative pathological examination. Results 45 pairs of EGC cases before and after eradication were enrolled. All the confidence level of DL (High confidence: 15.6% vs. 93.3%, p value = 0.000) and invasion depth (High confidence: 37.8% vs. 80.0%, p value = 0.000) and histopathological classification (High confidence: 31.1% vs. 91.1%, p value = 0.000) were significantly improved after eradication. A higher confidence level of DL before eradication was correlated with severe atrophy score (p value = 0.036). The inter-observer agreements for DL, invasion depth, and histopathological classification were 0.85 and 0.75 and 0.78, respectively. Conclusions DL of EGC becomes much more apparent after eradication in the short-term. Eradication therapy is necessary even shortly prior to the procedure of endoscopic submucosal dissection (ESD) to help precise pre-procedure diagnosis and avoid incomplete resection.